Changing travel patterns in China during the early stages of the COVID-19 pandemic - Hamish Gibbs (Nature Portfolio, 2020)
COVID-19-related travel restrictions were imposed in China around the same time as major annual holiday migrations, with unknown combined impacts on mobility patterns. Here, the authors show that restructuring of the travel network in response to restrictions was temporary, whilst holiday-related travel increased pressure on healthcare services with lower capacity.